Study and measurements of the uranium and amorphous crystals concentrations in urine samples of breast cancer female patients - Shafik, Shafik S. (Iraqi Journal of Physics, 2019)
In this work, Kinetic Phosphorescence Analyzer (KPA) has been used to measure the concentrations of uranium (UC) and Amorphous crystals (AMO) in urine samples of breast cancer patients in Baghdad. Additionally, a relation between UC and AMO with respect to patient’s age has been deduced and studied. Forty one urine samples of patients and five for healthy were taken from females lived in different residential area of Baghdad. The measured maximum UC value for urine samples of patients was 2.35 ± 0.053, the minimum value was 0.86 ± 0.034 μg/L, and an overall average was 1.6 ± 0.027 μg/L while the average UC for healthy females was 1.03 ± 0.020 μg/L. From these results, AMO concentrations were found for all breast cancer patients although those patients had not suffered from any kidney function. While all healthy women that tested against uranium and AMO, have been shown zero AMO. Further, UC increases with aging of patients and more incidence of breast cancer of females between the ages 40-59 years. Whereas the value of average AMO independents on the age of patients and also independents on the average value of UC, so the average of AMO is about "+++" for all patients’ groups.